2016
DOI: 10.1159/000445120
|View full text |Cite
|
Sign up to set email alerts
|

No Evidence of Human Polyomavirus 9, WU and KI DNA in Kidney and Urinary Bladder Tumour Tissue Samples

Abstract: Background/Aims: The oncogenic potential of human polyomaviruses (HPyVs) has been proposed, but so far only Merkel cell carcinoma polyomavirus seems to be associated with a human tumour. The role of BK polyomavirus (BKPyV) in human tumourigenesis remains controversial. BKPyV establishes persistent infection in the urinary tract, and renal and bladder neoplasms have been studied extensively, but conflicting prevalence data are reported. KI, WU and HPyV9 were detected in urine samples suggesting that these virus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 64 publications
0
9
1
Order By: Relevance
“…Protocols for KIPyV and WUPyV qPCR and positive controls were the same as described previously [39]. Plasmid-containing KIPyV isolate Stockholm 60 and AP-p002 plasmid with the half-genome of WUPyV were kindly provided by Tobias Allander and David Wang.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Protocols for KIPyV and WUPyV qPCR and positive controls were the same as described previously [39]. Plasmid-containing KIPyV isolate Stockholm 60 and AP-p002 plasmid with the half-genome of WUPyV were kindly provided by Tobias Allander and David Wang.…”
Section: Methodsmentioning
confidence: 99%
“…Colombara et al [31, 32] found that previous infections with these polyomaviruses were not associated with lung cancer. The DNA prevalence of KIPyV and WUPyV was studied in different cancer types [9, 11-13, 33-39], but only KIPyV was detected in lung carcinomas [11] and in benign skin tumours [35]. To date, the DNA prevalence of MWPyV was examined and detected in tonsillar cancer [9], but it was not found in mucosal melanoma [33].…”
Section: Introductionmentioning
confidence: 99%
“…So far, whether BKPyV has a causal role in the development of cancer was controversial. Early studies detected the presence of BKPyV large T antigens in prostate-, bladder- and kidney tumors [ 6 8 ], but several researchers thought BKPyV was unlikely to be involved in the etiology of most renal and bladder tumors because they had failed to detect BKPyV DNA in the cancer samples [ 9 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we tested this hypothesis, although we are not aware of any documented complementarity/synergy between polyomaviruses, as for instance has been described between DNA viruses, such as hepatitis B and D virus . At the same time, this approach offered the possibility to confirm our previously reported HPyV9 viremia rates in KTx patients, which were not found in a number of other comparable studies . Since TSPyV belongs to the same genus as HPyV9 (alpha polyomavirus), and is also detected in kidney tissue and urine, we included this polyomavirus in the analysis as well.…”
Section: Introductionmentioning
confidence: 99%
“…18 At the same time, this approach offered the possibility to confirm our previously reported HPyV9 viremia rates in KTx patients, which were not found in a number of other comparable studies. 15,19 Since TSPyV belongs to the same genus as HPyV9 (alpha polyomavirus), and is also detected in kidney tissue and urine, we included this polyomavirus in the analysis as well.…”
mentioning
confidence: 99%